Analisis Efektivitas Pelayanan E-Ktp Melalui Aplikasi Sibisa ( Studi Kasus Kantor Kecamatan Medan Marelan ) - Erini Putria; Bahrum Jamil; Nina Angelia (Universitas Medan Area, 2023)
The SIBISA application is a digital population administration and civil registration service application system using a papaerless office (PLO) and can integrate several service systems that have been built to become a synergistic and integrated service process based on the legal basis of Law no. 24 of 2013 related to the amendment of Law no. 23 of 2006 concerning population administration and civil registration. This study aims to determine the effectiveness of SIBISA services and the obstacles in implementing services in the Medan Marelan sub-district. This study uses a descriptive qualitative method that provides a clear description of the problems studied using Zeithaml's theory of public services with five service indicators, namely tangible, reliability, responsiveness, assurance and empathy. Data collection techniques used through observation, interviews and documentation. The results of this study indicate that the effectiveness of the E-KTP service through the SIBISA application in the Medan Marelan sub-district is quite effective compared to manual services starting from the services provided, the responsiveness of an employee to the community and the guarantee provided from the sub-district to the community through the management of the E-KTP. cannot be faked. The factors that affect the effectiveness of SIBISA services are computer networks, technical capabilities/skills of service providers and inadequate facilities and infrastructure.